Articulating Twintimacy as a Communicative and Cultural Perspective on Twinships. Issue 1 (2nd January 2020) - Allen, Jordan; Allen, Nicole; Moore, Julia
ABSTRACT: Unlike any other family relationship, twins are culturally understood as uncommon, special, and unique, while simultaneously in need of intervention to become separate, healthy individuals. Consequently, twins occupy a liminal cultural space where the spectacle of their relationship is praised and the intimacy of their relationship is often denigrated. To explore how individual twins navigate this double-bind, we adopted a cultural approach to examine the communicative constitution of intimacy in twin relationships (or twinships). Thirty-one twins participated in individual interviews about their relationship with their co-twin. Participant interviews indicated that twins make sense of their intimacy on a continuum of high and low levels of twintimacy, or intimacy of twin relationships characterized by individual and cultural constructions of twinships as extraordinary. Our findings revealed that twintimacy is both similar to and different from intimacy in singleton relationships. We discuss theoretical and practical implications of these results.